Homes by design concrete & glass. episode 603 - Jeans, Katherine (New York : Sound Venture Productions, 2007)
This programs show the concrete process in building a glass house
Title from title screen
Originally broadcast as an episode of the television program Homes by design
Executive producer, Neil Bregman ; editor, Michael Laeman
Narration: Tim Joyce
DVD format
Keywords: Glass construction; Concrete